REFORMULASI MADRASAH DALAM MEWUJUDKAN MADRASAH IBTIDAIYAH YANG BERDAYA SAING - Hilmi Qosim Mubah; Moh. Jani (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
Madrasahs still have many problems that need to be addressed, especially teacher problems. To create quality madrasahs, teacher professionalism is very important. The quality of teachers greatly impacts the quality of madrasahs, and professionalism is always related to welfare. This research is based on the instructions given by madrasah principals to teachers and education personnel through intense communication. The purpose of this study is to find out how teachers and madrasah principals handle problems; and to find out how teachers and madrasah principals build competitiveness. This study has a qualitative approach. Observation, interview, and documentation are the methods used to obtain data sources. Data sources included the Head of MI, student teachers, classroom teachers, and the community, and data were validated through triangulation and extended participation. The results of this study indicate that the role of the head determines the power or authority (power) to gather and mobilize all resources in the madrasah. The madrasah head also often provides supervision to educators and education personnel to actively participate in activities during class or outside the classroom. The madrasah principal must choose educators who are competent in their fields because teacher professionalism is important in the soul of an educator. They must also be able to choose or determine materials, as well as learning resources or the right media to facilitate the learning process.